Revision of the Oriental species of Apsilocera Bouček (Hymenoptera, Pteromalidae), with description of twelve new species - Mitroiu, Mircea-Dan; Achterberg, Cornelis Van (Zootaxa, 2013)
The Oriental species of Apsilocera Bouček, 1956 (Hymenoptera: Pteromalidae) are revised and the limits of the genus are reevaluated. Bulolosa Bouček, 1990 and Kratinka Bouček, 1988 are treated as synonyms of Apsilocera, syn. n. Bulolosa bidens Bouček and Kratinka brevis Bouček are transferred to Apsilocera as A. bidens (Bouček) and A. brevis (Bouček) comb. n., respectively. Twelve new species (all Mitroiu & van Achterberg) are described in Apsilocera: A. acuticristata sp. n., A. bicristata sp. n., A. cornuta sp. n., A. dentata sp. n., A. dupla sp. n., A. elongata sp. n., A. fulvipennis sp. n., A. longicornis sp. n., A. maculata sp. n., A. obtusicristata sp. n., A. palliclava sp. n., and A. tuberculata sp. n. An illustrated key to the females and males of Oriental species is provided.